Association of alcohol use disorder on alcohol‐related cancers, diabetes, ischemic heart disease and death: a population‐based, matched cohort study. (26th August 2021) - Leong, Christine; Bolton, James M.; Ekuma, Okechukwu; Prior, Heather J.; Singal, Deepa; Nepon, Josh; Konrad, Geoffrey; Paillé, Michael; Finlayson, Greg; Nickel, Nathan
Abstract: Background and aims: High‐risk alcohol consumption is associated with compromised health. This study aimed to compare the incidence of alcohol‐related cancers, diabetes, ischemic heart disease (IHD) and mortality between those with and without an indication of alcohol use disorder (AUD). Design: Retrospective, population‐based, matched cohort study using data from the Manitoba Population Research Data Repository. Rates were modeled using generalized linear models with either negative binomial distribution or Poisson distribution and a log offset of person‐years to account for each person's time to follow‐up. Setting: Manitoba, Canada. Participants: Individuals aged ≥ 12 years with a first indication of AUD (index date) between 1 April 1990 and 31 March 2015 were matched to five controls based on age, sex and geographical region at index. This study included 53 410 individuals with AUD and 264 857 matched controls. Measurements: Adjusted rate ratios (aRR) and 95% confidence intervals (CI) were determined for each outcome from 5 years prior to and 20 years after AUD detection. Findings: Alcohol‐related cancers (aRR = 4.85, 95% CI = 3.88–6.07 and aRR = 1.85, 95% CI = 1.35–2.53 for men and women, respectively), diabetes (aRR = 1.74, 95% CI = 1.50–2.02 and aRR = 2.43, 95% CI = 2.20–2.68) and IHD (aRR = 3.59, 95% CI = 3.31–3.90 and aRR = 2.92, 95% CI = 2.50–3.41) peaked in the 1 year prior to index for those with AUD compared with matched controls. All‐cause mortality (aRR = 3.31, 95% CI = 3.09–3.55 and aRR =3.61, 95% CI = 3.21–4.04) was highest in the year of index and remained higher among cases compared with controls throughout the 20‐year follow‐up. Conclusion: People with alcohol use disorder appear to have higher rates of adverse health outcomes in the year before alcohol use disorder recognition, and death at the time of alcohol use disorder recognition, compared with matched controls.